Bankster's Paradise: The Importance Of Discourse In Creating A Haven For Criminogenic Banks In The United States - Bordt, Maria Jacqueline (2014)
This work examines the ways in which language can contribute to a cultural climate in which white-collar crime is no longer considered deviant, but rather is considered part of a normally functioning political economy. The 2012 money laundering case involving HSBC is examined in conjunction with the rhetoric of popular financial counselor Dave Ramsey. This research seeks to define how language involving the accumulation of capital is equated with virtuousness, thus constructing a myth about the criminality inherent to legitimate capital enterprises